Analysis of Bank Muamalat's Performance Based on The Financial Ratio and Shariah Maqashid Index - Azmy, Ahmad; Astania, Levira; Triwanto, Triwanto (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This journal analyzes Bank Muamalat's performance based on the financial ratio and the Sharia Maqashid Index for the 2014 period to 2022. This study aims to assess the financial stability of the bank and their obedience to Islamic principles. The results of the financial ratio research: this condition is still in a reasonable condition, because the quick ratio value is still below 3, with a value of 0.20 when compared to existing standards that are in ROA ≤ 1.5% which means the bank is ineffective and efficient, ROE is 2 , 78 at Muamalat Bank which is below 12 shows that the ability of banks to generate profits by using equity owned by banks in bad conditions, net interest margin of the bank is at the value of NIM ≥ 2% means the condition of a healthy company, 97, 36% Bopo value ≤ ≤ 100% means that the company's health condition in carrying out its activities is efficient, with a value of 90.30 in a composite ranking position 3 (85% FDR ≤ 100%), which means the ability of bank liquidity to anticipate the liquidity needs and determination of adequate liquidity risk management. This study uses a quantitative analysis method to analyze financial data from the annual report of the Muamalat Bank. This journal also includes a qualitative assessment of Islamic banking practices and its impact on performance. The findings of this study will provide valuable insights for Bank Muamalat.